External Audit of School Improvement: Teachers Estimations Research - Balčiūnas, Sigitas; Blinstrubas, Artūras (Acta Paedagogica Vilnensia, 2006)
External Audit of School Managemcnt anei Educational Proceeding Improvement (ASMEPI) is a new method of education quality management. The method has been taken from Scotland and was applied in 2004-2005 for first time in Lithuanian educational system. The main empirical research question is how do teachers, who have been participated in ASMEPI, value the ASMEPI process as the instrumentality for improving secondary school. The focus group method has been applied in the research. Teachers of eight Lithuanian secondary schools were the subjects of the research. Procedures of data collecting have been started in a few days after the audit was finished. Results of the research show the structure and the expression of teachers’ estimation about ASMEPI in different schools. The proposition categories have been segregated applying deeper data analytical procedures. The categories show the participated teachers’ positive and negative experiences, the ASMEPI advantages and failings also. Teachers’ favourable perceptions about ASMEPI create assumptions: a) to implant the external audit into the education system as a modern concept of school evaluation; b) to change the conflict practice between estimators and those who are being evaluated developing the dialog type relationship in Lithuanian educational system, e) to strengthen teachers’ internal motivation to raise their qualification, d) to improve school proceeding.